O SESI-SP em suas entrelinhas: uma investigação interdisciplinar no Centro Educacional SESIS 033 - Souza, Mariana Aranha de (2006)
This research tried to investigate the Educational Centre SESI 033, in Tremembé from an interdisciplinary sight. A research group was made in which the work phases were socialized as they evolved. Its speeches and representations tried to understand the group of teachers characteristics mainly in their educative way. During the process it was necessary the investigation about the Institution´s Curriculum in which the school is insert, the Rede Escolar SESI-SP. Such investigation drew the educational trajectory of the Institution, through its historical process. The documental analysis allowed not only the discovery of historical aspects explicit in the Entity, but also important moments for the comprehension of education that one owes and its meanings in the school environment. Following the legislation changes it tried to adjust to the new requirements bringing about the own Curriculum references. The interdisciplinary way proposes a dialog between the subjects presented in this document, finding shining points, in which they share their theoretical principles. The teachers present their stories an find themselves as writers, and responsible for the take off of an Interdisciplinary project. Such way is only possible beginning with the interdisciplinary conception an category of action real as in the classroom everyday. They are issues that don t become extinct, by the contrary they show ways for an interdisciplinary contamination inside the Elementary Education Schools